2005
DOI: 10.1097/01.mlg.0000161356.35697.f6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diced Cartilage Graft Wrapped in Surgicell and Diced Cartilage Graft Wrapped in Fascia: An Experimental Study

Abstract: This study suggests that diced cartilage graft wrapped in surgicell was absorbed, whereas diced cartilage graft wrapped in fascia was not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 13 publications
3
33
0
Order By: Relevance
“…If it is used with fascia instead of surgicell, its permanence rate may be higher than 60%. 20 In conclusion, diced cartilage was found more reliable than bone dust aspect of preserving its volume for a long period in this study. If bone dust is used alone or with another autogenic material, serious resorption of filling material will be an evitable result.…”
Section: Discussionsupporting
confidence: 49%
“…If it is used with fascia instead of surgicell, its permanence rate may be higher than 60%. 20 In conclusion, diced cartilage was found more reliable than bone dust aspect of preserving its volume for a long period in this study. If bone dust is used alone or with another autogenic material, serious resorption of filling material will be an evitable result.…”
Section: Discussionsupporting
confidence: 49%
“…Following the use of Surgicel Ò -wrapped diced cartilage grafts and nasal dorsal augmentation, fascia-wrapped and block-form grafts were introduced and successful results have been obtained [3,4]. Later studies reported that damage to the cartilage or the use of Surgicel Ò or other alloplastic materials can increase the rates of resorption [5][6][7]17], and thus alternatives were needed.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that the use of oxidized regenerated cellulose to wrap diced or crushed cartilage grafts demonstrated no evidence of proliferation, thus reducing their clinical predictability because of negative effects on cartilage viability and regeneration. This might be related to the finding that Surgicel cellulose fibers persist for long periods of time after insertion in humans and that Surgicel is degraded by foreign body reaction rather than by hydrolyzed absorption 1 . Humans do not possess a hydrolytic enzyme for metabolizing cellulose 16 .…”
Section: Discussionmentioning
confidence: 99%
“…However, these grafts tend to return to their original conditions years after implantation. This leads to postoperative distortions and deformities 1,2 . It was Erol's 3 modification of diced cartilage grafting for dorsal nasal augmentation that recently popularized the use of these grafts.…”
Section: Introductionmentioning
confidence: 99%